Head and Brain Trauma among Children and Adolescents at a Public Hospital in Recife, Brazil - Orestes-Cardoso, Silvana; Aragão-Neto, Adelmo Cavalcanti; Orestes-Cardoso, Antonio Jorge; Lôbo, Jackson Santos; Silva, Josimário João; Farias, Alan Bruno Lira (Revista de Ciências Médicas e Biológicas, 2013)
<!–[if gte mso 9]> <![endif]–> Introduction: The Head and Brain Trauma (HBT) have a great potential to cause sequelae, therefore extremely important for the health professionals. Objective: The aim of this paper is to provide an epidemiological overview about HBT in a high complex health unit located in Recife, PE, Brazil. Methodology: Risk factors were divided in: Urban Violence (Road accidents, Running Over, Firearm, Physical aggression and Melee weapon) and Non-Urban Violence (Falls, Accidental Trauma, Sports and others). Statistical analysis was performed using descriptive and inferential techniques, such as: Fisher exact test, Chi-square test, and likelihood-ratio test. The statistical significance was set at 5%. Results: HBT was present in 5.5%, predominantly between ages ranging of 0 to 19 years old (17.6%). In this amount, the male gender had higher values than female, being the most affected the age ranging from 15 to 19 years, presenting a ration of 2.4:1. Concerning etiological factors, Non-urban-violence was present in 87.8%, occurring predominance in age ranging from 0 to 1 year old (96.2%). Conclusion: It was found prevalence of accidents among the male gender, which is a constant observed also in several other studies, however, a more alarming factor is the high rate of accidents involving young children, being indispensable the parents necessity of work, they received only essential care, being under the tutelage of older brothers, neighbors, and even non-nuclear relatives. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>